2012
DOI: 10.4081/or.2012.e4
|View full text |Cite
|
Sign up to set email alerts
|

The use of recombinant human bone morphogenetic protein-2 for the treatment of a delayed union following femoral neck open-wedge osteotomy

Abstract: Although the clinical potential of bone morphogenetic proteins (BMPs) has been known for decades, their use in humans has only been approved for a limited number of orthopaedic conditions. Promising results in animals demonstrate the utility of BMP-2 in regional bone repair without using osteoconductors. To our knowledge, no comparable human case has been described. We report the case of a 50-year-old who suffered a femoral neck fracture. After 9 months of extensive treatment, he was still not pain-free. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Previous studies reported that the incidence rate of delayed union after fracture and non-union was approximately 5-10%, and treatment of this remains a big problem in the field of orthopedics (8)(9)(10). In the BMP family, BMP2 is the main signaling protein regulating bone formation (11)(12)(13). BMP2 could induce differentiation of pluripotent mesenchymal progenitor cells into osteoblast cells, promoting bone forma-tion of osteoblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the incidence rate of delayed union after fracture and non-union was approximately 5-10%, and treatment of this remains a big problem in the field of orthopedics (8)(9)(10). In the BMP family, BMP2 is the main signaling protein regulating bone formation (11)(12)(13). BMP2 could induce differentiation of pluripotent mesenchymal progenitor cells into osteoblast cells, promoting bone forma-tion of osteoblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors that increase bone formation, such as VEGF, PDGF, and BMPs, are available for treatment. Among these, the osteogenic efficacy of BMPs has been reported in many studies (Baltzer et al 2012). We reported the osteogenic effect of recombinant human BMP-2 for delayed union in dogs (Kim et al 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…The results of immunohistochemistry in the current study support the findings of some experiments which showed that ESW treatment significantly upregulated the expression of BMP-2 in some musculoskeletal diseases. [34353637] Ras protein and BMP increased by the shock waves treatment were found to induce the differentiation of undifferentiated mesenchymal cell into cells capable of osteogenesis and promote the formation of bone and cartilage. [38] Meanwhile, the results of the present study showed roughly focused ESWT to be effective in the treatment of osteoporotic fractures by inhibiting bone resorption and increasing bone formation by enhancing OPG and BMP-2.…”
Section: Discussionmentioning
confidence: 99%